Safety in the operating theatre – Part 2: Human error and organisational failure(*) - Reason, J (BMJ Group, 2005)
Over the past decade, anaesthetists and human factors specialists have worked together to find ways of minimising the human contribution to anaesthetic mishaps. As in the functionally similar fields of aviation, process control and military operations, it is found that errors are not confined to those at the "sharp end". In common with other complex and well defended technologies, anaesthetic accidents usually result from the often unforeseeable combination of human and organisational failures in the presence of some weakness or gap in the system's many barriers and safeguards. Psychological factors such as inattention, distraction and forgetfulness are the last and often the least manageable aspects of the accident sequence. Whereas individual unsafe acts are hard to predict and control, the organisational and contextual factors that give rise to them are present before the occurrence of an incident or accident. As such, they are prime candidates for treatment. Errors at the sharp end are symptomatic of both human fallibility and underlying organisational failings. Fallibility is here to stay. Organisational and local problems, in contrast, are both diagnosable and manageable.